Mathematical competencies in the digital era - Stacey, Kaye (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2023)
The paper begins with a discussion of the characteristics of digitization that influence school mathematics, its goals and practices: the digitization of everything, the invisibility of computation, the era of big data and information on everything, and changes in the social role of mathematics due to increased global competitiveness. This leads directly to Theme 1, where we discuss the diminished economic and personal value of the ability to carry out routine mathematical procedures from arithmetic to calculus. Two other themes are then discussed: the reorientation of school mathematics content to support students to solve real world problems, and the need for students to understand about how mathematics can provide insight into real world problems, even when they are not able to actually do this themselves. These themes are only three of the many aspects of mathematical competence in the digital era which might have been chosen for discussion.